2007
DOI: 10.1080/02692170701474686
|View full text |Cite
|
Sign up to set email alerts
|

The Malaysian Real Trade Balance and the Real Exchange Rate

Abstract: The cointegration technique is used to examine the long‐run and short‐run relationships between the real Malaysian trade balance with the real exchange rate, domestic and world incomes. The results suggest that a real ringgit exchange rate depreciation improves the trade balance in the long run. World and domestic incomes are also found to be important determinants of trade balance. The significance of world income on trade balance indicates that Malaysia is prone to external shocks. An error‐correction model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…In section III we present our results mostly 1 For a review article on the Marshall-Lerner condition see Bahmani-Oskooee and Hegerty (2013). Note that Lal and Lowinger (2001), Duasa (2007) and Yusoff (2007Yusoff ( , 2010 have estimated aggregate trade balance of Malaysia with the rest of the world and have found no significant link between the exchange rate and Malaysia's trade balance. This maybe an indication of violation of the Marshall-Lerner condition.…”
Section: Introductionmentioning
confidence: 99%
“…In section III we present our results mostly 1 For a review article on the Marshall-Lerner condition see Bahmani-Oskooee and Hegerty (2013). Note that Lal and Lowinger (2001), Duasa (2007) and Yusoff (2007Yusoff ( , 2010 have estimated aggregate trade balance of Malaysia with the rest of the world and have found no significant link between the exchange rate and Malaysia's trade balance. This maybe an indication of violation of the Marshall-Lerner condition.…”
Section: Introductionmentioning
confidence: 99%
“… For a comprehensive review of articles related to Malaysia's trade balance see Bahmani‐Oskooee and Harvey (). In summary, Lal and Lowinger (), Duasa () and Yusoff (, ) report no significant link between the exchange rate and Malaysia's aggregate trade balance with the rest of the world. However, Wilson (), Onafowora () and Bahmani‐Oskooee and Harvey () who considered Malaysia's bilateral trade balances found some mixed results.…”
mentioning
confidence: 96%
“… It should be indicated that Lal and Lowinger (), Duasa () and Yusoff (, ) have used aggregate trade flows of Malaysia with the rest of the world and have found little support for the J‐curve effect. Bilateral trade flows of Malaysia with some of its partners have been considered by Wilson (), Onafowora () and Bahmani‐Oskooee and Harvey (), again with mixed findings.…”
mentioning
confidence: 99%